Young Children's spelling representations and spelling strategies. (December 2016) - Critten, Sarah; Sheriston, Lee; Mann, Franceska
Abstract: While traditional models of spelling describe the skills and knowledge required for development, the underlying cognitive processes that drive spelling success are often overlooked. Ninety-six English-speaking children, aged 5-to-7 years, completed two tasks which provided a direct measure of their spelling recognition and spelling production, respectively. Using a combination of performance measures and self-explanations, we assessed the relationship between children's performance on both the recognition and procedural tasks. Two separate hierarchical cluster analyses identified distinct profiles based on children's spelling recognition and spelling production, respectively. While these different profiles appeared related, log-linear analysis confirmed that the relations between recognition and production profiles were strongly moderated by children's spelling experience. Overall, the findings provide further support for application of the Representational Redescription (RR) and Overlapping Waves (OW) models in relation to young children's spelling acquisition within an English orthography. Highlights: Relations between spelling recognition and spelling production was explored. Justifications and self-explanations were used to classify 6-to-8 year olds' spelling recognition and spelling production. Distinct and partially ordered profiles in spelling recognition and production were identified. While recognition and production profiles appeared related, these were moderated by spelling experience and year group.